Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Mountea (Studi pada Konsumen di Bandung) - Septiyani, Denik; Sarah, Siti (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research was conducted to identify the influence of product quality and promotion on Mountea’s purchasing decisions (study of consumers in Bandung). The population used in this research is Mountea consumers in Bandung, totaling 96 respondents. The method used in this research is multiple linear regression analysis. The independent variables in this research are product quality and promotion. The dependent variable in this research is the purchasing decision. Data is collected through two sources: questionnaires as primary data and research via online sites. Data analysis includes a number of statistical methods, such as analysis of the coefficient of determination and hypothesis testing, both partially and simultaneously. The research results show that product quality and promotion partially positively and significantly influence purchasing decisions. Apart from that, product quality and promotions also have a positive and significant influence on purchasing decisions. The contribution of the independent variables (product quality and promotion) to purchasing decisions is 74.7%. Product quality is an independent variable that has a dominant influence on purchasing decisions.